My Heavens - Rogers, Gordon (Springer, 2017)
Perhaps you are already a stargazer using a small telescope you bring out to your back yard on clear nights. Perhaps you have a larger telescope that is mounted outside and protected from inclement weather. Perhaps you just dream of someday owning a fancy telescope set-up and turning it skyward to view the neighboring planets and moons of the Solar System or the stars that wink at you from millions of miles away.